The Impact of Night Shift, Work-Life Balance, and Ergonomic Factors on Occupational Accident Risk with Compliance to Safety Protocols - Tjiknang, Muhammad Abbyzard Dava; Suhardi, Suhardi; Kurniadi, Dedi (Economic: Journal Economic and Business, 2025)
This study aims to analyze the impact of night shifts, work-life balance, and ergonomic factors on the risk of workplace accidents, with compliance to safety protocols as a mediating variable. The research was conducted on 154 respondents working in high-risk sectors. Data analysis was carried out using Partial Least Squares Structural Equation Modeling (PLS-SEM) with the SmartPLS 4 software. The results show that night shifts have a significant and positive effect on the risk of workplace accidents. Meanwhile, work-life balance and ergonomic factors significantly influence compliance with safety protocols. However, compliance with safety protocols does not significantly affect the risk of accidents, and thus does not mediate the relationships between the other variables in the proposed model. These findings highlight the importance of better-managed night shift systems and the reinforcement of ergonomic conditions and work-life balance in ensuring a safe working environment. The practical implications call for managerial interventions and holistic occupational safety policies. Future studies are recommended to include additional variables such as job stress or safety culture, and to consider mixed-method approaches for a more comprehensive understanding.